Impact of iso- and low-osmolar iodinated contrast agents on BOLD and diffusion MRI in swine kidneys - Haneder, Stefan; Augustin, Jill; Krämer, Bernhard; Schönberg, Stefan; Meyer, Mathias; Attenberger, Ulrike; Michaely, Henrik J. M. (Investigative radiology, 2012)
Purpose: To assess whether functional MR imaging using blood-oxygenation level-dependent (BOLD) imaging and diffusion-weighted imaging demonstrate changes in renal oxygenation and apparent diffusion coefficient (ADC) in a pig model. Materials and Methods: After administration of either 1-g iodine/kg body weight low-osmolar iopromide or iso-osmolar iodixanol, 8 mini pigs underwent a series of repeated BOLD measurements (TR/TE 106/5.9-48.7 ms, slice thickness 4 mm) and diffusion-weighted imaging measurements (TR/TE 3900/79 ms, slice thickness 4 mm) for 1 hour at 1.5 T. In this intraindividual cross over study, the second contrast agent injection with the other iodinated contrast agent was performed at least 24 hours after the initial contrast agent injection. BOLD-based R2* values as indirect measures of the renal oxygenation were determined for the cortex, the inner medulla, and the outer medulla. ADC values were measured for the cortex and the whole kidney. Results: For both contrast agents, a drop in R2* was found in the cortex, which normalized after 55 minutes. In the outer medulla and particularly in the inner medulla, a decreased initial drop of R2* was encountered with both contrast agents, with a slow increase toward the baseline R2*. In the inner medulla, elevated R2* values were found with the iso-osmolar contrast agent only. The ADC revealed an initial increase, which slowly decayed over the measurement period. This finding was more pronounced for the cortex compared with the whole-kidney analysis. Conclusion: Functional MR imaging of the kidneys demonstrates increased R2* in the inner medulla only after the administration of the iodixanol potentially indicating hypoxia and thus a pathomechanism of contrast-induced nephropathy.
Gesehen am 23.07.2018